The Evaluation of Implementation of Operational Program Environment in the Programming Period 2007-2013 from Regional Aspect - Kováčik, Vladimír
The environment determines the quality of life in regions. Since Slovakia has joined EU, she has the right to draw financial support from EU resources in the area of cohesion and structural policy. The impact of the implementation of the Operational Program Enviroment for years 2007-2013. Better conditions of components of the environment for lives of people and business activities.